A flexible speller based on time-space frequency conversion SSVEP stimulation paradigm under dry electrode - Zhang, Ze; Li, Dandan; Zhao, Yao; Fan, Zhihao; Xiang, Jie; Wang, Xuedong; Cui, Xiaohong (Frontiers in Computational Neuroscience, 2023)
Speller is the best way to express the performance of brain-computer interface (BCI) paradigm. Because of the advantages of short analysis time and high accuracy, set, the SSVEP paradigm has been widely used in the BCI speller system based on the wet electrode. It is widely known that the wet electrode operation is cumbersome and the subjects have a poor experience. In addition, In the asynchronous SSVEP system based on threshold analysis, the system flickers continuously from the beginning to the end of the experiment, which leads to visual fatigue. The dry electrode has simple operation and a comfortable experience for subjects. The EOG signal can help subjects reduce fatigue. Therefore, this work firstly designed the brain-controlled switch based on the EOG signal of continuous blinking to improve the flexibility of the BCI speller. Secondly, in order to increase the number of speller instructions, we designed the time-space frequency conversion (TSFC) SSVEP stimulus paradigm by constantly changing the time and space frequency of SSVEP sub-stimulus blocks, and designed a speller in a dry electrode environment. Seven subjects participated and completed the experiments. The results showed that the accuracy of the brain-controlled switch designed in this study was up to 94.64%, and all the subjects could use the speller flexibly. The designed 60 characters speller based on TSFC-SSVEP stimulus paradigm has an accuracy rate of 90.18% and an information transmission rate (ITR) of 117.05 bits/min. All subjects can output the specified characters in a short time, which opens the way for the subsequent portable human-computer interaction.